Given that I = 0 ∫ ∞ ( x 2 1 − cos ( 3 4 2 x ) ) 2 d x = A π . Find A .
Bonus Find the closed form of 0 ∫ ∞ ( x 2 1 − cos ( α x ) ) 2 d x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice Solution!!
I think another (much more computational) way to do this is to set the bounds of the integral from 0 to N (for N large),and then differentiate under the integral with respect to alpha four times. Then compute this integral w.r.t. x. Then integrate four times to get the integral in question. (You will have to use that the sinc function integrated twice is cosine plus the integral of the sinc function.) Finally send N to infinity to get the answer (using that the integral of sinc from 0 to Infinity is Pi/2).
Log in to reply
This would work, but I would not want to perform all those calculations, since there would be a shed-load of terms coming from the fact that the integral is from 0 to N , not ∞ . In addition, you would have to pay careful attention with the potential for singularities at y = 0 .
I think we can also solve this with contour integration. Here is my solution:
Sources: Stein et al. Complex Analysis
Hint:The answer is written in his profile.
Problem Loading...
Note Loading...
Set Loading...
The function f ( x ) = { 2 π ( α − ∣ x ∣ ) 0 ∣ x ∣ < α ∣ x ∣ > α has Fourier transform ( F f ) ( y ) = 2 π 1 ∫ − ∞ ∞ f ( x ) e − i x y d x = y 2 1 − cos α y . Hence ∫ 0 ∞ ( y 2 1 − cos α y ) 2 d y = = = 2 1 ∫ − ∞ ∞ ∣ ∣ ( F f ) ( y ) ∣ ∣ 2 d y = 2 1 ∫ − ∞ ∞ ∣ ∣ f ( x ) ∣ ∣ 2 d x 4 1 π ∫ − α α ( α − ∣ x ∣ ) 2 d x = 2 1 π [ − 3 1 ( α − x ) 3 ] 0 α 6 1 π α 3 and so A = 6 1 α 3 . For this particular problem, we deduce that A = 6 1 × 4 2 = 7 .